Combinatorial optimization and applications : 9th International Conference, COCOA 2015, Houston, TX, USA, December 18-20, 2015, Proceedings /: 9th International Conference, COCOA 2015, Houston, TX, USA, December 18-20, 2015, Proceedings. (2015) - Unknown
No abstract available